Design and testing of a test rig for tubular joints hot-spot stress determination - Mohsin Iqbal; Saravanan Karuppanan; Veeradasan Perumal; Mark Ovinis; Muhammad Iqbal (Results in Engineering)
Circular hollow section (CHS) members are widely used in structural applications due to their high stiffness, low drag, uniform response under various loading directions, and aesthetically pleasing appearance. However, the complex stress and strain behaviour at the intersections of CHS members, known as tubular joints, is challenging to approximate analytically, necessitating numerical methods for analysis. Experimental validation of these models is essential but often requires sophisticated and costly setups that are not readily available. Although extensive research has been conducted on CHS joints, including validation of numerical and empirical models for determining stress concentration factors (SCFs), gaps remain in understanding SCF behaviour under complex loading scenarios. This study introduces a simplified test rig for investigating hot-spot stress and SCF behaviour in CHS joints for mono-, bi-, and tri-planar loading conditions. Loads are applied using dead weights, and responses are measured with strain gauges. The proposed setup has been validated against finite element analysis results. It accommodates joints made of various materials, such as steel, aluminium, or acrylic, and supports the investigation of SCFs under different combinations of axial, in-plane, and out-of-plane bending loads.